Agitated thin film drying of non-centrifugal sugars: Impact of processing parameters on the crystallinity and dissolution rates of NCS powder. (April 2023) - Iyer, Sneha R.; Mahajani, Sanjay M.
Abstract: In the present work, we have evaluated the application of Agitated thin film dryers (ATFD) to produce non-centrifugal sugars. Both crystallization and drying, performed otherwise as separate steps in the conventional process, are carried out together in ATFD, thereby making it a compact and cost-effective process. The powder obtained in ATFD was extremely dry (moisture content ∼ 3%) with a semi-crystalline form (<60% crystalline). The critical process parameters such as juice feed concentration and feed flow rates were optimized to get the NCS powder of varying crystallinity. The crystalline properties of the NCS powder were determined using X-ray diffraction and sorption isotherms. A product with as low as 37% crystallinity with low moisture (3% w/w) was realized with a dilute feed of 30 °Brix. Higher feed flow rate failed to achieve phase transition and resulted in a concentrated syrup of 50–75 °Brix. The product had unique characteristics in terms of amorphous nature with very low moisture content imparting a longer shelf life when compared to solid NCS blocks available in local market. The amorphous nature of NCS from ATFD makes it a fast-dissolving product with a dissolution rate of 22 mg ml −1 min −1 . Such a product can be conveniently used as an alternative sweetener in beverages, pre-mixes, and confectioneries. Highlights: Novel approach of using ATFD process to produce fast dissolving NCS powder. Highly amorphous and extremely dry NCS powder obtained from ATFD process. Feed concentration affects the crystallinity, sorption isotherm, and dissolution rates of NCS powder. Comparison of NCS powder from ATFD, conventional process, and market sample.